2020
DOI: 10.37349/emed.2020.00015
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and metabolic factors: the perfect combination to treat metabolic associated fatty liver disease

Abstract: The prevalence of nonalcoholic or more recently re-defined metabolic associated fatty liver disease (MAFLD) is rapidly growing worldwide. It is characterized by hepatic fat accumulation exceeding 5% of liver weight not attributable to alcohol consumption. MAFLD refers to an umbrella of conditions ranging from simple steatosis to nonalcoholic steatohepatitis which may finally progress to cirrhosis and hepatocellular carcinoma. MAFLD is closely related to components of the metabolic syndrome and to environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 208 publications
(277 reference statements)
0
10
0
Order By: Relevance
“…A common SNP (C47T, rs4880) determines a single amino acid (Ala16Val) replacement in the signaling sequence of the enzyme, reducing its function in the mitochondrial matrix. In this way, MnSOD can influence the genetic susceptibility to NASH, due to a lack of cell detoxification from the superoxide anion and an increased hepatocellular exposure to oxidative damage [356,357]. Evidence of the relationship between C47T SNP and NAFLD evolution came from a study that demonstrated how the increase in mitochondrial OS, resulting from this genetic predisposition, increases the fibrosis stage and, therefore, is associated with a more advanced NAFLD [358].…”
Section: Single Nucleotide Polymorphismsmentioning
confidence: 99%
“…A common SNP (C47T, rs4880) determines a single amino acid (Ala16Val) replacement in the signaling sequence of the enzyme, reducing its function in the mitochondrial matrix. In this way, MnSOD can influence the genetic susceptibility to NASH, due to a lack of cell detoxification from the superoxide anion and an increased hepatocellular exposure to oxidative damage [356,357]. Evidence of the relationship between C47T SNP and NAFLD evolution came from a study that demonstrated how the increase in mitochondrial OS, resulting from this genetic predisposition, increases the fibrosis stage and, therefore, is associated with a more advanced NAFLD [358].…”
Section: Single Nucleotide Polymorphismsmentioning
confidence: 99%
“…Familial, twin, and epidemiological studies indicated that NAFLD has a strong heritable component, which contributes to the huge inter-individual phenotypic variability. Dongiovanni et al demonstrated that hepatic fat accumulation represents the main driver of the progression to the end-stage of liver damage in genetically predisposed individuals, and recently proposed a detailed review including all the candidate genes related to NAFLD susceptibility [ 195 , 196 ].…”
Section: The Link Among Nafld Mitochondrial Dysfunction and Hcc: The Relevance Of Geneticsmentioning
confidence: 99%
“…PNPLA3 is mainly localized on the ER and LDs surface in hepatocytes, adipocytes and HSCs, and it may be transcriptionally induced or post-translationally modified to provide TG hydrolysis during the post-prandial or hyper-insulinemic state. Patients carrying the G allele lost PNPLA3 enzymatic activity, which impedes TG disposal and interferes with the activity of other lipases, such as PNPLA2 [ 196 , 197 ]. Beyond the triacylglycerol remodeling, PNPLA3 exerts widespread effects on human liver metabolome [ 198 ], influencing mitochondrial functions, glucose reprogramming and tumorigenesis.…”
Section: The Link Among Nafld Mitochondrial Dysfunction and Hcc: The Relevance Of Geneticsmentioning
confidence: 99%
“…HEY1 transcriptionally represses PINK1 in Huh7, reduced mitochondrial mass and altered inner cristae morphology [171]. review including all the candidate genes related to NAFLD susceptibility [199,200].…”
Section: The Impact Of Hypoxia On Hepatic Metabolic Reprogramming Andmentioning
confidence: 99%
“…PNPLA3 mainly localized on ER and LDs surface in hepatocytes, adipocytes and HSCs and it may be transcriptionally induced or post-translationally modified to provide TG hydrolysis during post-prandial or hyperinsulinemic state. Patients carrying the G allele lost PNPLA3 enzymatic activity, which impedes TG disposal and interferes with the activity of other lipases as PNPLA2 [200,201]. Beyond the triacylglycerol remodelling, PNPLA3 exerts widespread effects on human liver metabolome [202], influencing mitochondrial functions, glucose reprogramming and tumorigenesis.…”
Section: The Impact Of Hypoxia On Hepatic Metabolic Reprogramming Andmentioning
confidence: 99%